Original paperSerum soluble interleukin-6 receptor concentration measurement in patients with systemic sclerosis before and after immunosupressive therapy - Lis-Święty, Anna; Rogala-Poborska, Iwona; Syguła, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
The aim of this study was to asses the usefulness of soluble interleukin-6 receptor (sIL-6R) concentration in assesment of disease severity and treatment effects in systemic sclerosis (SSc) using immunosupressive agents. Seventeen patients with rapidly progressive SSc were treated with oral cyclophosphamide and prednisone for 6–60 months. The concentration of sIL-6R was measured by ELISA in the preatretment and posttreatment serum samples from the SSc patients and from 15 healthy women as controls. Pretreatment and postretment mean level of sIL-6R was significantly increased compared with normal controls, p<0.05 and p<0.001 respectively. Mean level of sIL-6R in SSc after treatment was significantly increased compared with that of before therapy, p<0.01. Serum levels of sIL-6R correlated positively with skin score before treatment (p<0.05). No correlation was found between sIL-6R levels and skin score after treatment, Raynaud’s phenomenon or cutaneous sclerosis and therapy duration. These findings do not encourage the application determination of sIL-6R concentration in serum for monitoring treatment effects in SSc.